Adaptation to resistance training - Wackerhage, H.; Atherton, P. (Genetics and molecular biology of muscle adaptation, 2006)
CHAPTER CONTENTS Learning Objectives 197 Inducing Skeletal Muscle Growth by Resistance Training 197 Resistance Training in Human Beings 198 Signalling Mechanisms in Anabolic Response to Resistance Training 200 Search for the Anabolic Signal 202 Skeletal Muscle Growth Factors 204 Global Transcriptional Regulation 208 Activation of the mTOR Signalling Cascade 209 Satellite Cell Proliferation andDifferentiation 216 Key Points 219 References 219